2015
DOI: 10.1111/epi.13013
|View full text |Cite
|
Sign up to set email alerts
|

Clobazam: An effective add‐on therapy in refractory status epilepticus

Abstract: SUMMARYRefractory status epilepticus (RSE) is a medical emergency, with significant morbidity and mortality. The use and effectiveness of clobazam, a unique 1,5-benzodiazepine, in the management of RSE has not been reported before. Over the last 24 months, we identified 17 patients with RSE who were treated with clobazam in our hospital. Eleven of the 17 patients had prior epilepsy. Fifteen patients had focal status epilepticus. Use of clobazam was prompted by a favorable pharmacokinetic profile devoid of drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 13 publications
(26 reference statements)
0
35
1
Order By: Relevance
“…Review of the literature showed different success rates than those just described. For example, the success rate in the second study seems much lower than the success rate described in the first study . This was also evident after correcting for the definition of success because CLB was the last antiseizure medication in 16 of 17 patients (94%) in the first .…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Review of the literature showed different success rates than those just described. For example, the success rate in the second study seems much lower than the success rate described in the first study . This was also evident after correcting for the definition of success because CLB was the last antiseizure medication in 16 of 17 patients (94%) in the first .…”
Section: Discussionmentioning
confidence: 77%
“…Finally, the second study excluded patients with focal RSE without impairment of awareness, absence RSE, and RSE secondary to anoxic brain damage, whereas the first study did not exclude these patients. In fact, 88% of the patients in that study had focal SE, making it difficult to compare these two cohorts and different success rates …”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Given its distinct 1,5‐benzodiazepine structure, CLB displays unique properties when compared to other commonly used benzodiazepines (BDZs) . Recent evidence has shown that clobazam may demonstrate therapeutic efficacy in status epilepticus (SE) . CLB's rapid and complete absorption, minimal drug interactions, low propensity for sedation, and possibility of being administered by enteral feeding tube without affecting its absorption make CLB a plausible option in the setting of SE .…”
mentioning
confidence: 99%